An empirical study of bank stress testing for auto loans - Wu, Deming; Fang, Ming; Wang, Qing (Journal of Financial Stability, 2018)
We present an empirical study of stress testing for portfolios of auto loans. We find that loans aged five years or more have significantly higher default probabilities. This finding raises concerns about the increasing maturity of auto loans in recent years. A challenge in stress testing is the instability of the estimated coefficient of macroeconomic variables, which raises questions on the reliability of stress test results. For this reason, it is important for model developers to perform sensitivity analyses and make conservative adjustment to minimize model risk.